lnternalization of Moral Values in Different Types of School - Martišauskienė, Elvyda (Acta Paedagogica Vilnensia, 2002)
The type of school has a significant influence on the process of internalization of leamers’ moral values. On the cognitive level this process is most successful in the learners of catholic, comprehensive and village schools. On the emotional level the results of different types of school are more alike and the differences are not so clearly marked. Moral values give least joy to the learners of sport schools, youth and the humanitarian type of schools. The learners of humanitarian type of school are the ones who consider their behaviour adequate to the moral standards. Young sportsmen display the best-balanced attitude towards both their believed moral values and their evaluation of their own moral behaviour. Essential differences between the type of school and learners’ estimation of altruism, responsibility, sensitivity, honesty, solidarity, dignity, and faith were found, as well as the tendencies of relationships between micro and macro surroundings (with God, friends, one’s self, nation, mother) were established.